FACTORS AFFECTING PERFORMANCE SMALL-SCALE AQUACULTURE PONDS IN PANGKEP DISTRICT - Sari, Purnama; Azis, Muhammad; Dunakhir, Samirah (RADJA PUBLIKA, 2023)
This research is entitled Factors Affecting the Performance of Small Business Pond Fisheries in Pangkep Regency. This research was conducted to reveal and provide solutions to the factors that affect the performance of small-scale aquaculture ponds in Pangkep Regency. The location of this research is in Pangkep Regency. This type of research is included in quantitative with a form of survey research, which is a method used to reveal the facts of a phenomenon using a questionnaire as a primary data collection tool. The research design is grouped into descriptive analysis to provide an overview of the distribution of data on various variable characteristics of factors related to phenomena that occur factually based on the perceptions of small-scale fisheries ponds in Pangkep Regency. Factors raised Karkateristik Entrepreneurship, Marketing Strategy and Government Regulation against small businesses of pond fisheries in Pangkep Regency. Sample withdrawal is done by using Probability sampling technique. Prerequisite data analysis using homogeneity test to determine whether some population variants are the same or not. The simplest normality test is to make a frequency distribution graph on existing scores. Descriptive statistical analysis to provide an overview of the variable factors that affect the performance of aquaculture ponds in Pangkep Regency and Inferesial statistical data analysis using Comfirmatory Factor Analysis